Pengaruh Rasio Keuangan, Ukuran Perusahaan Dan Biaya Agensi Terhadap Financial Distress - Deanisyah Suryani Putri; Erinos NR (Universitas Negeri Padang, 2020)
This study discusses financial comparisons, company size and agency costs to financial difficulties. The sample used in this study is a retail company listed on the Stock Exchange in 2016-2018 with a sampling method that is purposive sampling, so a sample of 19 companies is obtained. This study uses logistic regression data analysis techniques. The results showed that profitability, liquidity had a significant negative effect and leverage had a significant positive effect on financial distress, while company size and agency costs had no significant effect on financial distress.